Application of lean to the bidding phase in building construction: a French contractor's experience. Issue 2 (5th June 2017) - Dakhli, Zakaria; Lafhaj, Zoubeir; Bernard, Marc
Abstract : Purpose: While many procurement systems govern the construction sector, Design/Bid/Build is still prominent among the French building actors. The research applies Lean thinking (via a kaizen event) to the bidding phase of a building construction company to improve its bidding outputs. Design/methodology/approach: The method used in this study is "Action-Research". A two-month preparation phase was needed to prepare for the kaizen event. The results were based on an assessment conducted after 6 months of the kaizen event. Performance was measured following selected indicators related to 'Time', "Economical Impact", "Quality" and "Sustainability". Findings: The Lean implementation had positive side-effects on the company's organization and strategy as well. Practical implications: The findings of this action-research project can be used to help researchers and practitioners assess the potential application of Lean in the bidding phase. It also provides insights into the importance of the cultural and existing practices for a successful Lean implementation. Originality/value: A few research projects investigated the application of Lean thinking in bidding as it is considered as a wasteful process. However, waste can also be organized. The research proves that bidding can benefit from Lean thinking.